2008
DOI: 10.1007/s10048-008-0138-0
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of PARK genes in a Korean cohort of early-onset Parkinson disease

Abstract: Mutations in five PARK genes (SNCA, PARKIN, DJ-1, PINK1, and LRRK2) are well-established genetic causes of Parkinson disease (PD). Recently, G2385R substitution in LRRK2 has been determined as a susceptibility allele in Asian PD. The objective of this study is to determine the frequency of mutations in these PARK genes in a Korean early-onset Parkinson disease (EOPD) cohort. The authors sequenced 35 exons in SNCA, PARKIN, DJ-1, PINK1, and LRRK2 in 72 unrelated EOPD (age-at-onset ≤50) recruited from ten movemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
71
3
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(82 citation statements)
references
References 29 publications
4
71
3
3
Order By: Relevance
“…In conclusion, dosage mutations are relatively common in Brazilian early onset PD patients. The frequency observed by our study was similar to others from the literature [6,13,16]. PARKIN presented the majority of dosage alterations compared with the other known PD genes, as expected, while PINK1, SNCA and DJ-1 exon rearrangements were less common.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In conclusion, dosage mutations are relatively common in Brazilian early onset PD patients. The frequency observed by our study was similar to others from the literature [6,13,16]. PARKIN presented the majority of dosage alterations compared with the other known PD genes, as expected, while PINK1, SNCA and DJ-1 exon rearrangements were less common.…”
Section: Discussionsupporting
confidence: 79%
“…We identified a heterozygous deletion in exon 4 of PARKIN gene in one patient who has a juvenile AAO of 12 years and no family history of the disease. This alteration had already been reported by other groups in PD patients and healthy individuals [3,6,15,22]. Kay and colleagues (2010) demonstrated that heterozygous dosage mutations in exons 2-4 are common and well-tolerated in control subjects [15].…”
Section: Discussionmentioning
confidence: 81%
“…Out of the three missense mutations, the first identified, p.A53T, seems to be by far the most frequent one and was found in one Italian, eight Greek, two Korean, and one Swedish family (Polymeropoulos et al 1997;Athanassiadou et al 1999;Spira et al 2001;Ki et al 2007;Choi et al 2008;Puschmann et al 2009). The p.A30P and p.E46K mutations were identified in one family each (Kruger et al 1998;Zarranz et al 2004).…”
Section: Monogenic Forms Of Pdmentioning
confidence: 99%
“…The authors observed the presence of the mutation in several members of those 7 families, showing autosomal dominant inheritance pattern. Choi et al 26 identified the A53T mutation in only 1 of 72 patients with early-onset PD, whose family history was consistent with autosomal dominant PD.…”
Section: Discussionmentioning
confidence: 99%